Convulsive and Neurodegenerative Effects in Rats of Some Isolated Toxins from the Tityus bahiensis Scorpion Venom. (24th October 2013) - Takeishi Ossanai, Luciene Toshie; Lourenço, Geane Antiques; Lebrun, Ivo; Abrahão Nencioni, Ana Leonor; Coronado Dorce, Valquiria Abrão
Abstract : Despite Tityus bahiensis being one of the most dangerous scorpions in Brazil, there are few studies about the effects of its venom, which acts mainly on the central nervous system. Previous studies demonstrated the convulsive ability of this venom. The present work aimed to study the hippocampal effects in rats of some toxins isolated from pool V, which induces a pronounced epileptogenic effect. The pool was separated by reverse-phase HPLC, and the peaks with higher yield (Tb V-1, V-5, V-24, V-27, and V-28) were used in the experiments. Cannulae and electrodes were implanted in the hippocampus of male Wistar rats (240–250 g). The animals were divided into six groups that received intracerebral injection of toxin solution (1 or 2  μ g/ μ L) or Ringer solution (control group), and they were submitted to behavioral, electrographic, and histological analysis. All toxins studied evoked electrographic and behavioral epileptic-like activity to different degrees. Moreover, the toxins V-1, V-24, and V-28 caused significant neuronal loss in CA4 ipsi- and contralateral hippocampal areas. These results suggest that toxins from T. bahiensis scorpion, when injected into the hippocampus, are able to act directly on the central nervous system inducing convulsive and neurodegenerative effects.